Green Management and Corporate Sustainability Outcomes: (A Systematic Review of ESG, Governance, and Triple Bottom Line Integration) - Mutmainna Rachman; Ismail Rasulong; Muhammad Yusuf (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
Green management has evolved from operational environmental practice into a strategic capability embedded in governance and organizational decision making. Yet evidence on its effects on corporate sustainability remains fragmented and context dependent. This study conducts a Systematic Literature Review following PRISMA 2020 using peer-reviewed studies indexed in Scopus and Web of Science. From 2,484 records, 32 studies were retained for in-depth synthesis. The evidence is organized into four themes: governance and leadership, sustainability reporting and disclosure credibility, operational integration through innovation, controls and human resource management, and sustainability outcomes involving trade-offs, non-linearities and risks. Green management generally improves ESG and Triple Bottom Line outcomes when supported by strong governance, credible disclosure and internal capabilities. However, the literature also identifies non-linear ESG-performance relationships, greenwashing risks and sectoral or institutional contingencies. Integrating resource-based, stakeholder, legitimacy, signaling and agency perspectives, the review conceptualizes green management as a multi-level organizational capability and identifies priorities for more comparable measurement, stronger causal designs and context-sensitive sustainability research.